A “GROTESQUE” ON ORHAN VELİ’S STEP: MUZAFFER TAYYİP USLU - Seda ÖZBEK (Fırat University, 2019)
Orhan Veli Kanık, who constitutes an important part with Grotesque movement in New Turkish poetry, has influenced countless poets. One of them is Muzaffer Tayyip Uslu. Being from Zonguldak, poet closes his eyes to the life at twenties because of tuberculosis. In this article, Muzaffer Tayyip Uslu is attempted to be introduced with examples from his life, literary characteristics and poems.